2009
DOI: 10.14198/ingeo2009.49.07
|View full text |Cite
|
Sign up to set email alerts
|

Análisis comparativo de tendencias en la precipitación, por distintos inputs, entre los dominios hidrológicos del Segura y del Júcar (1958-2008)

Abstract: Recientemente han sido varios los trabajos que han analizado las tendencias en la precipitación dependiendo del tipo de flujo que la ha producido. Esta metodología novedosa ya se ha aplicado en el análisis de las precipitaciones en la Comunidad Valenciana, según tres tipos sinópticos básicos que las provocan: 1) precipitaciones convectivas, 2) de tipo frontal, y 3) las advecciones mediterráneas (Frente de Retroceso), detectándose tendencias significativas que no habrían sido detectadas con otro enfoque o metod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 3 publications
(5 reference statements)
1
5
0
2
Order By: Relevance
“…Yet if we take into account the results made available by studies conducted in the area on the observed series and precipitation types, a worrying scenario emerges in light of the results presented herein. They precisely indicate negative trends in precipitation toward the inland and hilly parts of the region (the Iberian System), which match the areas with the highest rise in temperature (SDSITVC), as opposed to littoral areas (Millán et al, 2005;Estrela et al, 2010;Miró et al, 2010;Miró et al, 2015). In fact, the total area occupied by the temperate macrobioclimate in the Iberian System section also could be in regression according to the additional data to Itc presented here.…”
Section: Discussionsupporting
confidence: 63%
“…Yet if we take into account the results made available by studies conducted in the area on the observed series and precipitation types, a worrying scenario emerges in light of the results presented herein. They precisely indicate negative trends in precipitation toward the inland and hilly parts of the region (the Iberian System), which match the areas with the highest rise in temperature (SDSITVC), as opposed to littoral areas (Millán et al, 2005;Estrela et al, 2010;Miró et al, 2010;Miró et al, 2015). In fact, the total area occupied by the temperate macrobioclimate in the Iberian System section also could be in regression according to the additional data to Itc presented here.…”
Section: Discussionsupporting
confidence: 63%
“…Particularly those studies published since 2000, which include more recent data and more spatial data, have detected structural changes in precipitation as a trend towards higher daily concentrations and greater irregularity [12,13], changes in their monthly and seasonal distribution [14][15][16][17][18][19] and dry periods lasting longer [20]. Therefore, it can be stated that change trends are underway [18] and are due to changes in both the frequency of atmospheric circulation patterns [16] and the synoptic mechanisms that generate precipitation in these basins [21][22][23]. These changes are solved with the presence of negative trends noted within the Júcar River Basin Authority (JHC) caused by loss of precipitation linked with Atlantic fronts [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be stated that change trends are underway [18] and are due to changes in both the frequency of atmospheric circulation patterns [16] and the synoptic mechanisms that generate precipitation in these basins [21][22][23]. These changes are solved with the presence of negative trends noted within the Júcar River Basin Authority (JHC) caused by loss of precipitation linked with Atlantic fronts [22,23]. These trends do not affect the littoral precipitations of both the studied basins (JHC and SHC; Júcar and Segura) because rain is linked with a Mediterranean genesis [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…En concreto, una tendencia al descenso de precipitaciones asociadas a frentes atlánti-cos de relativo mayor peso en el interior, que en el litoral se compensa por un aumento del peso relativo de las precipitaciones de origen mediterráneo (Millán, et al, 2005;Estrela et al, 2010;Miró et al, 2010;Miró et al, 2015). A ello se suma un cambio térmico mayor en las zonas altas del interior que en el litoral (Miró et al, 2015(Miró et al, , 2016a(Miró et al, y 2016b.…”
Section: Conclusionesunclassified
“…Se han determinado así tendencias al aumento de las temperaturas en el conjunto de la Península (p. ej., Brunet et al, 2007;Del-Río et al, 2012); y también cambios incipientes en los patrones de precipitación (Millán et al, 2005;Muñoz-Díaz y Rodrigo, 2006;Estrela et al, 2010;Miró et al, 2010;González-Hidalgo et al, 2010;Gallego et al, 2011). Sin embargo, se ha señalado que las mayores incertidumbres sobre los impactos del cambio climático se encuentran en los niveles regional y local (IPCC, 2013), lo cual es especialmente cierto para las regiones mediterráneas.…”
Section: Introductionunclassified